2015
DOI: 10.1021/acs.jced.5b00270
|View full text |Cite
|
Sign up to set email alerts
|

Viscosities of Liquid Cyclohexane and Decane at Temperatures between (303 and 598) K and Pressures up to 4 MPa Measured in a Dual-Capillary Viscometer

Abstract: The viscosities of cyclohexane and decane are reported at temperatures between (303.15 and 598.15) K and at pressures of (0.1, 1, 2, 3 and 4) MPa. The experiments were carried out with a dual-capillary viscometer that measures the ratio of the viscosities at temperature T and pressure p to that at a reference temperature of 298.15 K and the same pressure. Absolute values of the viscosity were then obtained with an expanded relative uncertainties at 95 % confidence of 3.0 % by combining the measured ratios with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The principle is based on Poiseuille’s law and the fact that the mass flow rates of the test fluid in the two capillaries are identical at a steady state. The working equation is as follows: Here, ρ T /ρ T 0 is the ratio of the densities at temperatures T and T 0 at the mean absolute pressure p M in the measurement capillary; S is a derivative (dΔ p /d Q ) of the pressure drop Δ p with respect to volumetric flow rate Q (measured at the pump conditions); and subscripts denote the reference capillary R, the measurement capillary M, and the relevant temperature. The quantity ( S R, T 0 / S M, T 0 ) cal is obtained in a calibration measurement with T = T 0 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle is based on Poiseuille’s law and the fact that the mass flow rates of the test fluid in the two capillaries are identical at a steady state. The working equation is as follows: Here, ρ T /ρ T 0 is the ratio of the densities at temperatures T and T 0 at the mean absolute pressure p M in the measurement capillary; S is a derivative (dΔ p /d Q ) of the pressure drop Δ p with respect to volumetric flow rate Q (measured at the pump conditions); and subscripts denote the reference capillary R, the measurement capillary M, and the relevant temperature. The quantity ( S R, T 0 / S M, T 0 ) cal is obtained in a calibration measurement with T = T 0 .…”
Section: Methodsmentioning
confidence: 99%
“…to account for secondary flow; 14,15 this factor is a function of the Dean number De and the ratio δ of the capillary radius to the coil radius.…”
Section: Apparatusmentioning
confidence: 99%
“…The viscosity data for CO2 was taken from a precise correlation having an estimated expanded relative uncertainty (k = 2) of approximately 3 % 71 as well as experimental data from Iwasaki and Takahashi 72 . The viscosity data of octane, decane, dodecane and m-xylene were original experimental data measured in our laboratory 18,[73][74][75] with estimated relative uncertainties of 2 %. These data span temperatures from (298 to 473)K and pressures from (0.1 to 200) MPa.…”
Section: Pure Fluidsmentioning
confidence: 99%
“…With this finding, we concluded that, by an appropriate scaling, the experimental data for each component can be collapsed onto a single curve relating reduced viscosity to residual molar entropy. Figure 4 Relative deviations Δη*/η* of the scaled reduced viscosity from the values estimated from equation (15) for each component: (a) decane: , Liu et al 74 ; , Caudwell et al 18 ; , Assael et al 77 ; , Carmichael et al 78 (b) m-xylene: , Caudwell et al 18 ; , Assael et al 30 ; , Et-tahir et al 80 Δη*/η* -S r /hR (e)…”
Section: Pure Fluidsmentioning
confidence: 99%
See 1 more Smart Citation